MACROGLOSSIA ASSOCIATED WITH PRIMARY SYSTEMIC AMYLOIDOSIS - CASE REPORT WITH UNUSUAL CLINICAL PRESENTATION - Suriyakala M; Leela Sreekantan Nair Sreela; Philips Mathew; Twinkle S Prasad; Admaja K Nair; Merrin Jose (Journal of Ayub Medical College Abbottabad, 2022)
Amyloidosis is characterised by the deposition of fibrillar insoluble proteinaceous material called amyloid in the extracellular spaces. It may present as localized form which is rare and systemic form. Systemic amyloidosis involves many organs like kidney, heart and liver. Manifestations of both types may vary based on the age of onset, degree and extension of the deposition. Understandably, the diagnosis is challenging but the early identification of the condition and the type of amyloidosis can increase the efficiency of treatment. Positive Congo red staining is the gold standard for demonstration of amyloid in tissue sections. Here we are presenting a case of a 77-year-old female patient who presented with the complaint of difficulty in swallowing for 2 years due to bilateral symmetrical enlargement of the tongue which was subsequently diagnosed as systemic amyloidosis.